The Duality Theory of Generalized Separated Continuous Linear Programming - Xiaoqing Wang (2010 International Conference on Management and Service Science, 2010)
In this paper, we consider a kind of new problem called generalized separated continuous linear programming (GSCLP), motivated by the great modeling power of it. By using discretization methodology, we prove that the strong duality holds between GSCLP and its dual under some mild condition.